GAINING BETTER INSIGHTS FOR LEARNING THROUGH THE USE OF MULTIPLE INTELLIGENCES IN CLASSROOMS - ISTI PURWANINGTYAS, M.Pd. (ISSN)
In gaining better insights for learning, both teachers and learners need to pay attention on the differences of learning styles in the classroom. This article tries to see the importance of taking learning styles into consideration, through the use of Multiple Intelligences theories, some approaches teachers could make to know their students better, and the problems of adapting MI in the class. Lastly, teachers do not necessarily need to always match the instructions to the learning styles, but more importantly they need to be creative in designing more activities to make students learn better.